Faktor yang Berhubungan dengan Perilaku Tidak Aman pada Pekerja di PT X - Budiman, Lia Aprilia; Wahyuningsih, Anik Setyo (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Unsafe action is a dangerous action that may be motivated by age, lack of knowledge and experience, fatigue, stress and others. At PT X there were 11 workers (73.3%) who took unsafe actions, including such as lack of awareness of the potential dangers of a work process, lack of knowledge and negligence of workers, use of personal protective equipment. This study aims to determine factors related to unsafe behavior in workers at PT X. Method: This type of research is observational analytic using a cross sectional design. Random sampling technique and a sample of 48 respondents. The research instrument used a questionnaire and used the Chi Square test. Results: There is a relationship between the variables age (p-value = 0.001), years of service (p-value = 0.006), work attitude (p-value = 0.007), Occupational Health and Safety (OSH) knowledge (p-value = 0.000), OSH supervision (p- value = 0.002), OSH training (p-value = 0.000), and availability of PPE (p-value = 0.022) are associated with unsafe behavior. There is no relationship between OSH regulations and unsafe behavior (p-value = 0.262) Conclusion: There is a significant relationship between age, years of service, work attitude, OSH knowledge, OSH supervision, OSH training, and availability of PPE with unsafe behavior in workers in PT X.